1995
DOI: 10.1148/radiology.195.1.7892451
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscesses: 13 years of experience in percutaneous needle aspiration with US guidance.

Abstract: US-guided PNA with antibiotic therapy in treatment for PLA is a valid alternative to prolonged catheter drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
2
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 0 publications
8
115
2
4
Order By: Relevance
“…Earlier studies had reported the mean TLC to be 15000cells/mm3 with the range 7500cells/mm3 to 25000cells/mm3. [8] Majority of our patients (86%) had single liver abscess cavity and 94% of our patients had their right lobe involved (Figure No 2).This finding is similar to other studies where solitary abscess and right lobe involvement were most commonly noted [9,10,12,16,17,18] In our study 68% patients had abscess size between 5-8 cm with a mean of 6.5±1.8 (Table 03).It was similar to other studies [6,15,17,19,20] In our study pus culture were positive in 80% patients with E.Coli in 40% cases, Kleibsiella in 10%, staphylococcus in 24% and mixed organism in 06% cases (table no 04). In our study Kleibsiella incidence was less probably due to exclusion of diabetic patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Earlier studies had reported the mean TLC to be 15000cells/mm3 with the range 7500cells/mm3 to 25000cells/mm3. [8] Majority of our patients (86%) had single liver abscess cavity and 94% of our patients had their right lobe involved (Figure No 2).This finding is similar to other studies where solitary abscess and right lobe involvement were most commonly noted [9,10,12,16,17,18] In our study 68% patients had abscess size between 5-8 cm with a mean of 6.5±1.8 (Table 03).It was similar to other studies [6,15,17,19,20] In our study pus culture were positive in 80% patients with E.Coli in 40% cases, Kleibsiella in 10%, staphylococcus in 24% and mixed organism in 06% cases (table no 04). In our study Kleibsiella incidence was less probably due to exclusion of diabetic patients.…”
Section: Discussionsupporting
confidence: 90%
“…[6,7] Ninety percent of our patients were male and 10% female .So male : female ratio is 9:1. Reports in the literature show there is a male preponderance in a ratio ranging from 10:1 to 17:1 [8,9,10].…”
Section: Discussionmentioning
confidence: 85%
“…4 With the development of new radiologic techniques, improvement in microbiologic identification, advancement of drainage techniques and operative procedures, the mortality rate has come down to 5-30%.Yet the incidence has relatively remained unchanged and with the treatment, the mortality has come down to normal in those patients attending to hospitals. 4 Most of the patients in present study with liver abscess were in middle age with patients in second to fourth decade accounting for55.2% of the cases which is comparable to other study done by Grorgia et al 5 Siddiqui et al reported that in case of ALA most common age group was 31-40 and in group of PLA 41-50 age group was more affected. 6 In our study there was high incidence of liver abscess in males (77.61%), as seen in a study by Huang et al (96%).…”
Section: Discussionsupporting
confidence: 85%
“…[1][2][3] In adults, imaging-guided percutaneous aspiration and insertion of a pigtail catheter in liver abscess is a well-accepted treatment modality. [2][3][4] Complications that can arise are; secondary infection, bleeding into the abscess cavity, inadvertent catheter misplacement into the IVC and rupture of abscess with spillage into the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Treatment of amebic liver abscess is mainly by anti-amebic drugs and percutaneous drainage of the abscess cavity. [1][2][3] We report a case of amebic liver abscess that presented with complications related to percutaneously inserted catheter drainage.…”
Section: Introductionmentioning
confidence: 99%